Efektivitas Pelatihan Tenaga Kesehatan dengan Metode Pembelajaran Full Online dan Blended di Balai Pelatihan Kesehatan Provinsi Sumatera Selatan - Kurniasih, Fonny; Sulastri, Sri; Hakim, Arif Rahman (Program Studi Magister Ilmu Administrasi Publik STISIPOL Candradimuka, 2023)
This research was motivated by the condition of the Covid-19 pandemic, there was a policy change that required us to be in a new condition, namely not being allowed to gather people in one place and close to each other because of physical distancing and social distancing in the long term. In the end the training applies a distance learning system (distance learning) by utilizing electronic learning technology. The purpose of this study was to determine the effectiveness of training with full online and blended learning methods. This thesis research uses qualitative methods. The data collection process was carried out using observation techniques, in-depth interviews, and documentation studies The results of this study speak volumes about the following matters, namely; a) Reaction is a measure of training effectiveness which can be seen from the reaction of the trainees, especially direct reactions; b) The Learning Process measures the effectiveness of the training based on how well the trainees are able to absorb the information provided during the training; c) This change in behavior is in the form of behavioral effects, namely changes in attitude that occur before and after training; d) Results of measurement of training efficiency in terms of achieving organizational goals, quality of work, time efficiency, quantity of output and reduction of waste.